2011
DOI: 10.1590/s0103-84782011005000042
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de acessos de bananeira com base na concentração de compostos funcionais

Abstract: O objetivo deste trabalho foi determinar a concentração de polifenóis totais, flavonóides, vitamina C e carotenóides totais em 61 acessos de banana pertencentes ao Banco Ativo de Germoplasma de bananeira da Embrapa Mandioca e Fruticultura. Foram detectadas diferenças significativas para todas as características analisadas por meio da análise de variância. A média para os teores de polifenóis totais entre os 61 acessos de banana foi de 38,06mg 100g-1, com variação de 12,51mg 100g-1 para o triplóide 'Torp' a 257… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…; among triploids, the means were 3.05 µg g -1 (AAA), 9.31 µg g -1 (AAB) and 3.15 µg g 1 (ABB) [23]. These values are similar to those of the present study with bananas 'Prata-Anã' in group AAB.…”
Section: Resultssupporting
confidence: 89%
“…; among triploids, the means were 3.05 µg g -1 (AAA), 9.31 µg g -1 (AAB) and 3.15 µg g 1 (ABB) [23]. These values are similar to those of the present study with bananas 'Prata-Anã' in group AAB.…”
Section: Resultssupporting
confidence: 89%
“…'Terrinha' also showed high carotenoid concentration, which was 14 times higher than that found in 'Caipira', and nine times higher than the concentration found in 'Marmelo', which resulted from high á-carotene and â-carotene concentrations. Amorim et al (2011) evaluated 62 banana accessions in Brazil -including improved and wild diploids, triploids and tetraploid hybrids -and found total carotenoid concentration ranging from 140 (AAA genotypes) to 1924 µg (100 g FM -1 ) (AAB genotypes). The lowest concentration was found in 'Caipira'.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with those of Viana et al (2013), who found a range from 1.20 µg g -1 to 2.62 µg g -1 , in improved and commercial genotypes. In turn, Amorim et al (2011b) observed wide variation in 61 banana genotypes, with total carotenoids ranging between 1.18 µg g -1 (Champa Madras) and 19.24 µg g -1 (Saney). The authors also found that…”
Section: Genotypementioning
confidence: 97%